16
Test 2 / Re: TT2-P2
« on: November 19, 2015, 01:04:42 AM »
I believe there may be a mistake in this one. As we did in HA7, we must change the given condition at $y=0$ by Fourier transform as well. So we will have (making use of the hint):
\begin{equation}
u|_{y=0} \longrightarrow \hat{u}|_{y=0} = \hat{\frac{1}{x^2 + 1}} = \frac{1}{2}e^{-|k|}
\end{equation}
We should be able to proceed similarly to what Xi Yue Wang has done, with the integral now being:
\begin{equation}
u(x,y)=\frac{1}{2} \int_{-\infty}^{\infty} e^{-|k|y}e^{-|k|}e^{ikx} dk
\end{equation}
It's actually a simple integral to solve; we split it up so that we have:
\begin{equation}
u(x,y)=\frac{1}{2} \left( \int_{-\infty}^{0} e^{ky}e^{k}e^{ikx} dk + \int_{0}^{\infty} e^{-ky}e^{-k}e^{ikx} dk \right)
\end{equation}
So we get:
\begin{equation}
u(x,y) = \frac{1}{2} \left( \frac{e^{ky+k+ikx}|_{-\infty}^0}{y + 1 + ix} - \frac{e^{-ky-k+ikx}|_{0}^{\infty}}{y + 1 - ix} \right)
\end{equation}
Evaluating, we get:
\begin{equation}
u(x,y) = \frac{1}{2} \left( \frac{1}{y + 1 + ix} + \frac{1}{y + 1 - ix} \right)
\end{equation}
The final answer is then:
\begin{equation}
u(x,y) = \frac{y+1}{(y+1)^2 + x^2}
\end{equation}
\begin{equation}
u|_{y=0} \longrightarrow \hat{u}|_{y=0} = \hat{\frac{1}{x^2 + 1}} = \frac{1}{2}e^{-|k|}
\end{equation}
We should be able to proceed similarly to what Xi Yue Wang has done, with the integral now being:
\begin{equation}
u(x,y)=\frac{1}{2} \int_{-\infty}^{\infty} e^{-|k|y}e^{-|k|}e^{ikx} dk
\end{equation}
It's actually a simple integral to solve; we split it up so that we have:
\begin{equation}
u(x,y)=\frac{1}{2} \left( \int_{-\infty}^{0} e^{ky}e^{k}e^{ikx} dk + \int_{0}^{\infty} e^{-ky}e^{-k}e^{ikx} dk \right)
\end{equation}
So we get:
\begin{equation}
u(x,y) = \frac{1}{2} \left( \frac{e^{ky+k+ikx}|_{-\infty}^0}{y + 1 + ix} - \frac{e^{-ky-k+ikx}|_{0}^{\infty}}{y + 1 - ix} \right)
\end{equation}
Evaluating, we get:
\begin{equation}
u(x,y) = \frac{1}{2} \left( \frac{1}{y + 1 + ix} + \frac{1}{y + 1 - ix} \right)
\end{equation}
The final answer is then:
\begin{equation}
u(x,y) = \frac{y+1}{(y+1)^2 + x^2}
\end{equation}